2018
DOI: 10.1021/acs.inorgchem.8b02684
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Site-Differentiated Fe4S4 and Fe6S6 Clusters

Abstract: Obtaining rational control over the structure and nuclearity of metalloclusters is an ongoing challenge in synthetic Fe-S cluster chemistry. We report a new family of tridentate imidazolin-2-imine ligands L(NIm R)3 that can bind [Fe4S4] 2+ or [Fe6S6] 3+ clusters, depending on the steric profile of the ligand and the reaction stoichiometry. A high-yielding synthetic route to L(NIm R)3 ligands (where R is the imidazolyl N substituents) from trianiline and 2-chloroimidazolium precursors is described. For L(NIm Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 82 publications
2
27
0
Order By: Relevance
“…At the center of the cofactor is a trigonal prism of 6 Fe centers surrounding an unprecedented interstitial carbon, with 3 ''belt sulfurs'' (denoted in yellow in Figure 2) bridging the two partial cubanes. Great strides toward synthesizing structurally accurate models of FeMoco have been made, [55][56][57][58][59] but these do not yet fully mimic the cofactor, especially with respect to the trigonal prism core.…”
Section: Structure and Properties Of The Femo-cofactormentioning
confidence: 99%
“…At the center of the cofactor is a trigonal prism of 6 Fe centers surrounding an unprecedented interstitial carbon, with 3 ''belt sulfurs'' (denoted in yellow in Figure 2) bridging the two partial cubanes. Great strides toward synthesizing structurally accurate models of FeMoco have been made, [55][56][57][58][59] but these do not yet fully mimic the cofactor, especially with respect to the trigonal prism core.…”
Section: Structure and Properties Of The Femo-cofactormentioning
confidence: 99%
“…Their 31 P NMR resonances (at 102.1 and 96.0 ppm for 4 and 5 , respectively) are shifted downfield from that of the free ligand 3 (−0.4 ppm), reflecting both the expected downfield shift upon binding a Lewis acidic metal center 32,33 and the population of paramagnetic excited states as is commonly observed in [Fe 4 S 4 ] 2+ clusters; 23,3438 their room-temperature solution magnetic moments (μ eff = 2.7 and 2.8 μ B , respectively) are consistent with this interpretation and typical of [Fe 4 S 4 ] 2+ clusters. 35,3941 The 1 H NMR signals corresponding to the −C H 3 and −C H 2 – protons of the ethyl ligand in 5 are observed at −4.6 and 70.0 ppm, respectively, which also indicates the population of paramagnetic excited states. 23,3438 Clusters 4 and 5 exhibit reversible, one-electron reduction events in their cyclic voltammograms at −1.48 and −1.78 V vs Fc/Fc + , respectively (see Supporting Information (SI)), reflecting the greater electron-donating ability of the ethyl ligand compared with that of the chloride.…”
mentioning
confidence: 97%
“…11) by adding Et 2 Zn to the [Fe 4 S 4 ] 2+ -Cl cluster. [115][116][117] Single-crystal X-ray diffraction revealed the Fe-C bond length in Fe-Et was 2.05 Å, which was comparable to that in a tris(thioether)borate-ligated Fe 2+ -Me complex (2.03 Å). 118 57 Fe Mössbauer spectra of [Fe 4 S 4 ] 2+ -Cl and [Fe 4 S 4 ] 2+ -Et clusters at 90 K and the calculations revealed that the positive charge was more localized on the apical iron site in the [Fe 4 S 4 ] 2+ -Et cluster due to the electron-donating ethyl group on the apical site.…”
Section: Studies Of Multinuclear Fe Sites As Models For N 2 Activationmentioning
confidence: 77%